A new perspective on the proper timing of radiotherapy during CDK4/6 inhibitor therapy in patients with "bone-only" metastatic breast cancer - Ilona Tornyi; Peter Árkosy; Ildikó Horváth; Andrea Furka; Andrea Furka (Frontiers Media S.A., 2023)
The vast majority of hormone positive and HER2 negative advanced breast cancers can be controlled well by endocrine therapy combined with the groundbreaking use of CDK4/6 inhibitors in the metastatic first-line setting. Approximately 50%-60% of these patients have "bone-only" metastatic disease. In oligometastatic cases or if a certain number of uncontrolled lesions develop during the aforementioned therapy, ablative radiotherapy can be delivered or, in symptomatic cases, urgent irradiation is needed with palliative intent. To achieve the most effective results, parallel with good quality of life, the timing of radiotherapy must be determined precisely, taking into account that different cell cycles are involved during different treatment modalities; therefore, optimization of treatment schedules ensures longer and safer post-progression overall survival. The key question is whether the two treatment modalities are safe concurrently or whether they should be administered separately, and if so, what is the optimal sequence and why? This manuscript aims to answer this important question, with a focus on quality of life. Existing publications focus on safety and toxicity profiles, and efficacy is detailed only tangentially and minimally.